Pengaruh Kompleksitas Daerah, Ukuran Pemerintah Daerah dan Pertumbuhan Ekonomi terhadap Kelemahan Sistem Pengendalian Internal Pemerintah Daerah - Melia Andesti; Henri Agustin (Universitas Negeri Padang, 2022)
The review is conducted with the purpose of acquiring empirical evidence related the effect of complexities of local goverment, the local size goverment and economic growth to internal control weakness. The population of this reseacrh are local goverment in Aceh and Sumatera Utara Province of 2017-2019. The sample were determined by using purposive sampling methode. Based on predetermined criteria, 156 local goverments hae been selected as samples.the kind of information use is secondary data from the report of local goverment finances from the audit board of BPK, and Gross Domestic Regional Product (PDRB) report. This reseacrh was carried out using multiple linear regression analysis with help of software SPSS version 25. The afterefects of this reseacrh showed that complexities of local goverment has a significant positive effect on internal control weakness, the local size goverment has a significant negative effect on internal control weakness. Meanwhile economic growth has not siginificant effect on internal control weakness.